Assessing short-term outcomes of carotid artery stenting at Hue Central Hospital - Hoang, Hai Phu; Le Vu Huynh, Pham Dinh Chuong (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
Stroke is an important medical problem in all countries of the world. Preventing stroke is a priority goal of community health programs and each individual. Carotid stenting is a less invasive alternative in comparison to surgery. This study was conducted on 19 patients with internal carotid artery stenosis, in which the stent was placed to recreate the flow, at Hue Central Hospital from January 2018 to January 2020. Results: Age was 61.1 ± 16.1 years, history of stroke was 57.9%, hypertension was 78.8%, dyslipidemia was 68.4%, smoking was 57.9%, and bilateral carotid lesion was 57.9%. The patients whose stenosis was ≥70% and ≥90% accounted for 100% and 47.4% respectively. The success of the procedure was 100%, and blood flow to the brain improved (36.7%). There was no case with dangerous events such as embolism, infarction, or cerebral hemorrhage. After 6 months, clinical outcomes and the prognosis improved according to NIHSS and mRS. No death or complication of cerebral infarction or cerebral hemorrhage was reported.